Development of work safety model for VDT workers using participatory approach - Suthakorn W. (2017)
Participatory approach is an intervention strategy that has been successfully used for public health implementation. This study applies this approach to help manage working related health problems in the workplace. The principle of this approach is to empower workers to participate identifying risk and injuries caused by physical exposure at work as well as proposing proper control measures. As the decision makers, workers are more apt to accept the intervention program and this may help sustain the change. © 2012 IEEE.